Relationship Among Sensory Over-Responsivity, Problem Behaviors, and Anxiety in Emerging Adults with Autism Spectrum Disorder - Syu YC; Huang PC; Wang TY; Chang YC; Lin LY (Neuropsychiatric Disease and Treatment, 2020)
Ya-Cing Syu,1 Pai-Chuan Huang,1 Tsui-Ying Wang,1 Yen-Ching Chang,1 Ling-Yi Lin1,2 1Department of Occupational Therapy, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 2Institute of Allied Health Sciences, College of Medicine, National Cheng Kung University, Tainan, TaiwanCorrespondence: Ling-Yi Lin Tel +886-6-235-3535 ext. 5917Fax +886-6-237-6604Email lingyi@mail.ncku.edu.twIntroduction: Despite the highly prevailing rate of sensory over-responsivity, problem behaviors, and anxiety among emerging adults with autism spectrum disorder (ASD), little is known about the nature of their experiences. While previous studies have indicated potential relationships among these conditions, their connections still need to be clarified. This study aimed to examine the relationships between sensory over-responsivity, problem behaviors, and anxiety.Methods: Fifty-seven emerging adults with ASD (Mage =  21.4, SD =  2.5; males =  80.7%) were recruited. The Adult Sensory Profile – Chinese version, Problem Behavior Scale of Scales of Independent Behavior – Revised, and Generalized Anxiety Disorder-7 – Chinese version (GAD-7) were used.Results: The percentage of emerging adults with ASD who scored more than most people in the two quadrants were sensation sensitivity = 33.3% and sensation avoiding = 26.3%. Approximately 66.7%, 27.5%, and 50.9% of participants had internalizing behaviors, externalizing behaviors, and asocial behaviors, respectively. Approximately, 64.9% of the participants scored on or above the cut-off score of 6 on the GAD-7. Sensation sensitivity and sensation avoiding were significantly correlated to problem behaviors; and anxiety was a mediating variable that accounts for the relationships between sensory over-responsivity and problem behaviors.Conclusion: These results indicated that emerging adults with ASD showing problem behaviors might also report more exaggerated responses toward sensory inputs and experience more anxiety symptoms. The results indicate that sensory over-responsivity, problem behaviors, and anxiety may have common underlying mechanisms. Findings can be useful to understand the impacts of such difficulties for emerging adults with ASD.Keywords: autism spectrum disorder, sensory over-responsivity, anxiety, problem behaviors